2008
DOI: 10.1038/jes.2008.60
|View full text |Cite
|
Sign up to set email alerts
|

Residual oil combustion: a major source of airborne nickel in New York City

Abstract: On the basis of previous observations that: (1) both the nickel (Ni) concentration in ambient air fine particulate matter (PM(2.5)) and daily mortality rates in New York City (NYC) were much higher than in any other US city; and (2) that peaks in Ni concentration was strongly associated with cardiac function in a mouse model of atherosclerosis, we initiated a study of the spatial and seasonal distributions of Ni in NYC and vicinity to determine the feasibility of productive human population-based studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 9 publications
1
42
0
Order By: Relevance
“…The results depicted in Figures 3 and 5 for Ni and V in Bronx, Manhattan and Northern Queens are consistent with those of Peltier et al (2008) that were based solely on EPA, STN, and IMPROVE speciation site data. The new data confirm our expectation that Ni concentrations in the more southern parts of NYC would be much lower than those in the more northerly parts of the city, and provide a much clearer picture of the extent of the spatial and seasonal distributions of the elemental concentrations of components associated with residual oil combustion.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The results depicted in Figures 3 and 5 for Ni and V in Bronx, Manhattan and Northern Queens are consistent with those of Peltier et al (2008) that were based solely on EPA, STN, and IMPROVE speciation site data. The new data confirm our expectation that Ni concentrations in the more southern parts of NYC would be much lower than those in the more northerly parts of the city, and provide a much clearer picture of the extent of the spatial and seasonal distributions of the elemental concentrations of components associated with residual oil combustion.…”
Section: Discussionsupporting
confidence: 77%
“…As discussed in our previous paper (Peltier et al, 2008), we showed that a variety of fuel oils are used in New York State for industrial, energy production, transportation, and spaceheating purposes. These fuels include both distillate and residual oils.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While local vehicular traffic was the largest source of ambient PM 2.5 mass in Cork Harbour during the sampling period, shipping traffic contributed significantly to ambient particle number concentrations (18%). Considering that fresh ship exhaust particles reside predominantly in the ultrafine mode and contain polycyclic aromatic hydrocarbons and transition metals with known toxicological effects, this source may have implications for human health in the area (Lippmann et al, 2006;Peltier et al, 2008;Murphy et al, 2009;Healy et al, 2009;Sodeau et al, 2009). …”
Section: Resultsmentioning
confidence: 99%